FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI PENGUSAHA KECIL (Studi di Wilayah KPP Pratama Semarang Candisari) - Efa Setiati Farahdina; Herry Laksito (Diponegoro Journal of Accounting, 2016)
To develop the infrastructure, Indonesia requires sources of funds both from national or international. The national funds mostly obtained from tax. Thus, the taxpayer is expected to have a high awareness of paying tax. However, many taxpayers are still not aware by not paying the tax on time or tend to avoid the tax. The aim of this research is to analyze the effect of perceived tax equity, normative expectations, legal sanctions, tax compliance intention, to tax compliance. The hypothesis that was proposed were perceived tax equity, normative expectations, legal sanctions have positive effect toward tax compliance intention. Also tax compliance intention has positive effect toward tax compliance.The sample of this study were small employer individual taxpayers who registered in KPP Pratama Semarang Candisari in 2014 by using purposive sampling. Methods of data collection is by using questionnaires of 100 respondents using a Likert scale of 1 to 5. Data analysis technique used is multiple linier regression.The results of this study indicate that (1) Perceived tax equity had a significant effect toward tax compliance intention, (2) normative expectations had a significant effect toward tax compliance intention (3) legal sanctions had a significant effect toward tax compliance intention (4) tax compliance intention had a significant effect toward tax compliance.